Rare-Earth Eu3+/Gold Nanocluster Ensemble-Based Fluorescent Photoinduced Electron Transfer Sensor for Biomarker Dipicolinic Acid Detection - Xiu, Ling-Fang (Langmuir : the ACS journal of surfaces and colloids, 2021)
The use of metal ions to bridge the fluorescent materials to target analytes has been demonstrated to be a promising way to sensor design. Herein, the effect of rare-earth ions on the fluorescence of l-methionine-stabilized gold nanoclusters (Met-AuNCs) was investigated. It was found that europium (Eu3+) can significantly suppress the emission of Met-AuNCs, while other rare-earth ions showed a negligible impact. The mechanism on the observed fluorescence quenching of Met-AuNCs triggered by Eu3+ was systematically explored, with results revealing the dominant role of photoinduced electron transfer (PET). Eu3+ can bind to the surface of Met-AuNCs by the coordination effect and accepts the electron from the excited Met-AuNCs, which results in Met-AuNC fluorescence suppression. After introducing dipicolinic acid (DPA), an excellent biomarker for spore-forming pathogens, Eu3+ was removed from the surface of Met-AuNCs owing to the higher binding affinity between Eu3+ and DPA. Consequently, an immediate fluorescence recovery occurred when DPA was present in the system. Based on the Met-AuNC/Eu3+ ensemble, we then established a simple and sensitive fluorescence strategy for turn-on determination of biomarker DPA, with a linear range of 0.2-4 μM and a low limit of detection of 110 nM. The feasibility of the proposed method was further validated by the quantitative detection of DPA in the soil samples. We believe that this study would significantly facilitate the construction of metal-ion-mediated PET sensors for the measurement of various interested analytes by applying fluorescent AuNCs as detection probes